Harvard Lycopolitan John – kolejne fałszerstwo? Koptyjski manuskrypt w świetle Ewangelii Żony Jezusa i współczesnych badań - Bąk, Tomasz Bartłomiej (The Biblical Annals, 2016)
On 18 September 2015, during the International Congress of Coptic Studies in Rome, Professor Karen L. King from Harvard Divinity School, presented a previously unpublished Coptic papyrus fragment, known as the Gospel of Jesus’ Wife. This text was among the scraps of ancient manuscripts, one of which is known as the Harvard Lycopolitan John and contains small fragments from the Gospel of John. In my article I attempt to analyze this second manuscript and demonstrate, on the basis of various scientific examinations performed by contemporary scholars, that the aforementioned Gospel of Jesus’ Wife, and also the Harvard Lycopolitan John, are modern creations. Unknown origin of the HLJ, unusual dimensions of the manuscript, dialectal implausibility, linguistic errors, etc. – all these phenomena allow us to treat the Harvard Lycopolitan John as a forgery, which was faithfully copied from Herbert Thompson’s 1924 edition of the fourth-century Lycopolitan “Qau codex”.